Stretchable, self-healing and biodegradable water-based heater produced by 3D printing. (June 2020) - Guo, Binbin; Zhang, Jingshi; Ananth, K. Prem; Zhao, Shuai; Ji, Xinzhu; Bai, Jiaming
Graphical abstract: Abstract: Common issues when realizing hybrid heaters for articular thermotherapy are the structural stability and limited lifetime when they are subjected to unavoidable mechanical manipulation during practical applications. Therefore, the objective of integrating multi-functionality with reliable performance has been pursued for a long time. To this end, we have designed a novel water-based hybrid heater utilizing a facile 3D printing technology of direct ink writing, thereby simultaneously realizing self-healing ability, mechanical stretchability, and biodegradability. Accordingly, the as-obtained devices demonstrated outstanding properties such as environmental friendliness and expanded lifetime, even under severe mechanical treatment. Owing to the introduction of conductive bridges formed between carbon nanotubes and graphene nanosheets inside the water-flour, the efficient Joule heat increased the temperature of the heater to 89.5 °C in 120 s at a bias of 20 V. Additionally, owing to its novel configuration, the proposed heater exhibited good temperature buffering, a property that is superior and absent in the traditional devices for articular thermotherapy. Finally, the system presented in this study is expected to serve as a model for the further design of multi-functional water-based hybrid heaters having economic and environmental applications.